Understanding Riba, Profit, And Fines in Sharia Banking - Setiawan, Rendra Noer; Muhajirin (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2024)
The debate and problem of riba, profit, and fines particular its practices in Sharia Banking among scholars, academics, the public, practitioners, business people, and religious organizations in Indonesia until now still reap a lot of opinions and controversy that affects the level of public trust in Sharia Banking, resulting in less growth in the market share of Sharia Banking compared to conventional banking even though Sharia Banking governance, performance, quality of compliance, image, and goodwill of Sharia Banking have adjusted to Islamic sharia. The research method used in this research is a literature study method that can be focused on the concept of usury, profit, and fines according to Sharia Banking. The results show that usury can be avoided through buying and selling transactions rather than lending and borrowing, but various understandings and information about usury do not necessarily advance the economy and Sharia Banking in Indonesia. The development of Sharia Banking faces various obstacles, including different understandings of usury among scholars, the public, business people, and a lack of encouragement from the government. Although the Sharia Banking system has been adapted to Islamic law, the market share of Sharia Banking in Indonesia is still relatively small, only 7.3% compared to conventional banking which reaches 92.7%. To increase the market share of Sharia Banking, it is necessary to increase public trust and awareness of Sharia Banking.